Pertanggungjawaban Tindak Pidana Kelalaian Lalu Lintas Oleh Anak yang Menyebabkan Orang Lain Meninggal Dunia (Studi Putusan Pengadilan Negeri No.212/Pid.B/2013/PN-PMS) - Jimmy Fernando Dapot Sianturi; Alvi Syahrin; Madiasa Ablisar; Sutiarnoto Sutiarnoto (Universitas Sumatera Utara, 2019)
Abstract. Criminal acts of negligence is a form of criminal acts with the error in the form of negligence. Error in omissions occur if the perpetrator does not use ability assets when that ability should be used.This research is to find out how the children criminal liability in the case of traffic accidents that certainly should pay attention to the best interests for the child. Keywords: Negligence, Children, Criminal Liability